Genetic predisposition to childhood obesity does not influence the risk of developing skin cancer in adulthood - Jay Keatley; Matthew H. Law; Mathias Seviiri; Catherine M. Olsen; Nirmala Pandeya; Jue-Sheng Ong; Stuart MacGregor; David C. Whiteman; Jean Claude Dusingize (Scientific Reports, 2024)
Abstract The relationship between body mass index (BMI) and melanoma and other skin cancers remains unclear. The objective of this study was to employ the Mendelian randomization (MR) approach to evaluate the effects of genetically predicted childhood adiposity on the risk of developing skin cancer later in life. Two-sample MR analyses were conducted using summary data from genome-wide association study (GWAS) meta-analyses of childhood BMI, melanoma, cutaneous squamous cell carcinoma (cSCC), and basal cell carcinoma (BCC). We used the inverse-variance-weighted (IVW) methods to obtain a pooled estimate across all genetic variants for childhood BMI. We performed multiple sensitivity analyses to evaluate the potential influence of various assumptions on our findings. We found no evidence that genetically predicted childhood BMI was associated with risks of developing melanoma, cSCC, or BCC in adulthood (OR, 95% CI: melanoma: 1.02 (0.93–1.13), cSCC 0.94 (0.79–1.11), BCC 0.97 (0.84–1.12)). Our findings do not support the conclusions from observational studies that childhood BMI is associated with increased risks of melanoma, cSCC, or BCC in adulthood. Intervening on childhood adiposity will not reduce the risk of common skin cancers later in life.